Performance Evaluation of Evaporative Cooling Systems as Alternative for Increasing the Shelf Life of Perishable Crops at the Farmer Level in Vunjo-Moshi Rural - Msacky , Nelson Joseph; Leonard, Leopord Sibomana (International Journal of Environment, 2023)
Postharvest handling in developing countries continues to be a major challenge for most of the farmers. The low economy in these countries is counted as a major obstacle toward the adaptation of modern postharvest technologies. The present study aimed to assess the existing post-harvest handling practises and test the suitability of evaporative cooling systems for reducing post-harvest losses by using Vunjo-Moshi Rural as a case study. A total of 30 questionnaires covering small commercial farmers were utilised to get information regarding the existing post-harvest handling practices in Vunjo. Two evaporative cooling systems, the Charcoal Cooler Chamber and Sand Cooler Chamber, were created and tested in Vunjo. Their effectiveness was measured by their response to temperature and humidity changes. Results indicated that 87% of the small farmers in Vunjo used local precooling and cold storage methods characterised by low efficiency. Further results showed 77% of all spoilage crops were randomly disposed of in the environment regardless of their impacts. Performance results of designed evaporative systems showed that the Charcoal Cooler Chamber (at its highest performance), could lower the daily ambient temperature by 8.8 °C while increasing the ambient relative humidity from 73.01% to 90.93%. The Sand Cooler Chamber could reduce the daily ambient temperature by 7.8 °C and increase the ambient relative humidity from 73.01% to 93.90%. The performance of both designed systems met the recommended standard for increasing the shelf life of most of the perishable crops cultivated in Vunjo, making them recommended as alternative precooling and cold storage technologies.